Teaching high school physics with a serious game - Stege, L.; van Lankveld, G.; Spronck, P. (International Journal of Computer Science in Sport, 2012)
This study explores the research domain of using serious games to support learning processes. In particular, we examined the effect of a serious game on teaching high school students electrical engineering theory. We compared the abilities of two groups of high school students to answer questions on this subject immediately after they received instructions on it. The first group received its instructions by means of a serious game, the second group by means of a text. We discovered that the group that received its instructions via a serious game performed significantly better than the text group in solving the assignments. Surprisingly, the group that received its instructions via a text indicated that they were better motivated. Further analysis revealed gender differences: males benefitted most from instruction via a serious game, while females were better motivated by a text. From our results we conclude that, at least in our application domain, serious games can be more effective in supporting the learning process than written texts, but that they do not necessarily motivate students better than a textbook.